Research Performance of CSIR-NEERI, Nagpur during 1989-2013:A Scientometric Study - Lohiya, Rajesh Kumar; Sengar, K. P. S.; Cyriac, Jiji (Journal of Information and Knowledge, 2016)
National Environmental Engineering Research Institute, Nagpur, a national laboratory under the CSIR (NEERI) plays an important role in the field of environmental engineering and science by providing innovative and effective solutions to a wide range of environmental problems in the country. This study attempts to analyze the research publications of CSIRNEERI, during the 25 year period between 1989 and 2013. The data for this study consists of details of 1236 publications that were extracted from Web of Science Database as well as Institute Annual reports. The publication data were analyzed on various parameters like, publication trend, highly cited papers, most prolific authors, collaborative authorship pattern and trends, the degree of author's collaboration and preferred journals for scholarly communication and so on. The study shows that the majority of the scientists preferred to publish research papers in joint authorship. The most preferred journal for publication by CSIR-NEERI scientists is Environmental monitoring and assessment.